Pengaruh Temperatur Kalsinasi Terhadap Gugus fungsi, Struktur mikro, Dan Kerapatan dislokasi Pada Material Katoda Baterai LiNiO2 - Budiarto (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2022)
Battery cathode material is one of the four determinants of energy storage capacity, which is used as a power source in electronic equipment. laptops, and electric vehicles. Synthesis of LiNiO2 battery cathode material by solid state method, and variations in calcination temperature from 700 oC,  775 oC, and 850 oC , as wll as a fixed time of 6 hours. The results of the analysis using the FTIR spectrum showed that the vibration mode correlated with the vibrations of the octahedral units of NiO6 and LiO6 in the wave number zone of 400 - 700 cm−1. Thus, the peak around 433 cm−1 is caused by the Li–O asymmetric strain vibration of LiO6 and the NiO6 bending vibration, namely [(Ni–O–Li)], occurring at 551-603 cm−1. The results of the observation of the microstructure with SEM showed the size of the micron with an uneven and homogeneous surface. The elemental compositions of Li and Ni metals were analyzed by EDXS showing that the metal content of Li and Ni decreased as the calcination temperature increased. The results of the crystal structure test using an X-ray diffractometer showed that with the increase in the calcination temperature, the average diameter of the crystallites decreased, but the average dislocation density increased and the mean micro-lattice strain also increased ( 0.4817% to 15.8079%) and in the Miller hkl index plane. (102), (104), (210), (108), and (113).